Mushkilāt Al-Talāmīdh fī Ta’allum Al-Nuşūş Al-‘Arabiyah fī Ma’had Bait Al-Raḥmān bi Sūmatrah al-Shamaliah - Batubara, Marlina; Triana, Hetti Waluati; Ritonga, Mahyudin (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2024)
Translation activities are often carried out by generation z in the field of education, generation z translates Arabic texts or books related to the material they are studying, so that it is easier to understand the material. However, the translation process does not always run smoothly. There are several problems they face when translating. This research was conducted to identify the difficulties faced by Generation Z when translating. This research uses a qualitative approach with analytical methods. The research subjects here are generation Z who are learning to translate. The author uses a questionnaire to find out the data and analyzes it using descriptive analysis. The results of this research are that there are problems translating Arabic texts for generation z in the Arabic language education study program. Penpen is influenced by linguistic and non-linguistic aspects. This research is motivated by the fact that generation Z is experiencing difficulties, one of which is a lack of understanding of the rules of the Nahwu. Mastering Arabic grammar and morphology is very important in learning the Arabic language, especially in translating it into other languages, so that there is an equal understanding of the meaning.